2021
DOI: 10.23887/jet.v5i1.33368
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Discovery-Based Virtual Laboratory Learning to Improve Student Science Process Skills

Abstract: The inadequate condition of the laboratory, facilities, and infrastructure is the main obstacle to the lack of practicum activities. The purpose of this study was to examine the effectiveness of discovery-based virtual laboratory learning in improving science process skills of students. This type of research is a one-group-pretest-postest design research. Population and sample taken were students who took Basic Chemistry II course. The data collection method was carried out in a documentary manner and data ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
11
0
3
Order By: Relevance
“…In addition, students can run simulations using their laptops, smartphones, or tablets anywhere. Nirmala & Darmawati (2021) also stated that students could be trained in several science process skills through virtual laboratory activities, making learning more exciting and fun. Most of students have science process skills in good categories after learning.…”
Section: Figure 2 Diagram Of Students' Science Process Skills Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, students can run simulations using their laptops, smartphones, or tablets anywhere. Nirmala & Darmawati (2021) also stated that students could be trained in several science process skills through virtual laboratory activities, making learning more exciting and fun. Most of students have science process skills in good categories after learning.…”
Section: Figure 2 Diagram Of Students' Science Process Skills Testmentioning
confidence: 99%
“…This study shows that students have the opportunity to improve the science process skills through investigation activities such as observation, formulating problems, hypnotizing, collecting data, testing hypotheses, and concluding. Also, Nirmala & Darmawati (2021) found that virtual laboratory learning has succeeded in improving students' science process skills.…”
Section: Introductionmentioning
confidence: 97%
“…Practicum plays a crucial role in face-to-face tutorials because it can provide students with scientific method training by following the instructions detailed in the instruction sheet. Practicum is a learning interaction between students and learning materials to observe and understand material about nature (Nirmala & Darmawati, 2021). By doing practicum, students will become sure of one thing.…”
Section: Introductionmentioning
confidence: 99%
“…Biology consists of theory and practical science. However, the Biology learning process will be more straightforward if the learning process is not only obtained through a collection of theories, laws, principles, and facts and related to how knowledge is obtained, namely by experiment (Ani Cahyadi et al, 2021;Nirmala & Darmawati, 2021;Selwyn & Renaud-Assemat, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many students struggle with formulating hypotheses, testing their theories, and completing practicums. In the conventional practicum, laboratory assistants will offer direct feedback when students make mistakes throughout the learning process (Almroth, 2015;Nirmala & Darmawati, 2021). However, in a virtual laboratory, lab assistants cannot accompany all students as they practice at home, and they do not receive feedback throughout the learning process when they misread data or lose vital knowledge (Bangert et al, 2022;Engzell et al, 2021).…”
Section: Introductionmentioning
confidence: 99%